Medição de produtividade na fabricação e montagem de estruturas pré-moldadas em concreto para apoio ao planejamento de curto prazo - Cruz, Weslley Machado da (2012)
The ever-increasing level of competitor efficiency and client’s requirement has led corporations to seek to improve their performance. Despite the efforts of academics, the use and understanding of management systems, particularly the concepts and practice of the performance measurement are not systematically applied largely by construction companies. The absence of adequate measures associated with corporate strategies has been identified as one of the greatest weaknesses in the management of the same. Due to the scenario and the lack of application of this theme under construction precast concrete technology, the objective this paper is to establish a system of measuring productivity in manufacturing and installation of precast concrete structures to shortterm planning support. This research is defined as an action-research conducted within a company producing structures precast concrete, located in Goiânia city metropolitan area, covering three cases studied. The work initially sought to develop a performance measurement system based on the deployment of productivity indicators related to services running and then adjust this measurement system to schedule both the factory and the construction site setting in supporting planning decisions and control for the company. Among the results of the study confirmed the subsidies planning phase of the construction with the indicators found, suggesting the reformulation of project planning from the consideration of performance measurements, and effective control of management processes.